STUDI KRITIS LEGISLASI DALAM PERUNDANG-UNDANGAN PERBANKAN SYARIAH - Abul Khair (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2017)
AbstractThe presence of sharia banking in Indonesia is just beginning to develop, following the issuance of Law no. 21 of 2008 on sharia banking, although it has been discourse long before the issuance of the Act, which is more than half a century ago. The delay is due to two things. The first is due to political issues. The labeling of